2023
DOI: 10.5603/fm.a2022.0095
|View full text |Cite
|
Sign up to set email alerts
|

The greater omentum and similar serous formations of testis in male white rats

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, the data presented in our publication on the consolidation of the greater omentum and serous formations of the epididymides, completely homologous to the latter (Hryn et al, 2022;Hryn et al, 2023b), with the perforated openings of the cecum have not been found in the scientific literature, as well as the morphological aspects of the local immune response to infection of the peritoneal cavity of the experimental animals.…”
Section: Discussionmentioning
confidence: 66%
“…However, the data presented in our publication on the consolidation of the greater omentum and serous formations of the epididymides, completely homologous to the latter (Hryn et al, 2022;Hryn et al, 2023b), with the perforated openings of the cecum have not been found in the scientific literature, as well as the morphological aspects of the local immune response to infection of the peritoneal cavity of the experimental animals.…”
Section: Discussionmentioning
confidence: 66%